USM SCHOOL OF MEDICAL SCIENCES LAUNCHES ITS DIRECTORY OF EXPERTISE - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
KUBANG KERIAN, KELANTAN, 11 September 2016 – The School of Medical Sciences (PPSP), Health Campus, Universiti Sains Malaysia (USM) recently launched the ‘Directory of Expertise' (www.medic.usm/expertsppsp (http://www.medic.usm/expertsppsp)) database at its website which provides a comprehensive list of its lecturers/academic staff/researchers and their areas of expertise within the medical field.